Simultaneously Quantification of Ethanamizuril Marker Residue in Edible Tissues of Chicken by Ultra-high Performance Liquid Chromatography–Mass Spectrometry - Liu, Yingchun; Zhao, Xiao; Wang, Chunmei; Zhang, Keyu; Zhang, Lifang; Wang, Mi; Fei, Chenzhong; Wang, Xiaoyang; Xue, Feiqun (Food analytical methods, 2020)
Ethanamizuril (EZL) is a novel anti-coccidiosis triazine compound synthesized in our laboratory. The marker residue of EZL in chicken tissues was EZL and its metabolite deacetylethanamizuril (deacetylEZL). In order to quantitatively analyze the EZL and deacetylEZL in chicken tissues, a rapid, simple, and specific ultra-high-performance liquid chromatography–mass spectrometry (UPLC-MS/MS) method was developed. Validation was performed according to the European Commission Decision 2002 /657/EC guidelines. The detection limit was 5 μg kg −1 , 10 μg kg −1 , and 5 μg kg −1 in muscle, liver, and skin+fat for EZL. And the detection limit of deacetylEZL was 2 μg kg −1 , 10 μg kg −1 , 2 μg kg −1 , and 10 μg kg −1 in muscle, liver, skin+fat, and kidney, respectively. The mean recoveries from fortified samples ranged from 80.15 to 99.50%, with inter assay coefficients of variation ranging between 5.03 and 15.84%. Based on this method, the depletion profile of EZL was studied in 60 healthy chickens after administration of 10 mg L −1 via drinking water for 3 days. Six medicated and one control chicken were sacrificed at 4, 8, 12, 24, 48, 60, 72, 96, and 120 h after the cessation of treatment. The highest residue concentrations of marker residue were attained at the first day, and those of all samples were below the MRL at 68.74 h post-treatment. The concentration of marker residue in kidney tissue was significantly higher than those in liver, skin+fat, and muscle tissues. The statistically estimated withdrawal period of EZL with oral administration was 4 days.